QUANTIFICATION OF ALUMINUM CONTENTS IN COOKED FOODSTUFFS FROM THREE REGIONS IN JAVA USING NEUTRON ACTIVATION ANALYSIS - Ahmad Hasan As'ari; Saeful Yusuf; Alfian Alfian (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2020)
Aluminum is widely available in nature and the third most abundant element on earth. Improper intake of aluminum can increase toxicity and correlate with Alzheimer's disease. One source of aluminum comes from food. In this study, aluminum content in foodstuffs was analyzed using neutron activation analysis. Various foodstuffs were purchased from markets in three regions in Java, namely Bangkalan (East Java), Magelang (Central Java), and Cianjur (West Java) and cooked at a temperature above 80°C until the ready-to-eat condition. The cooked samples were freeze-dried and irradiated in the G.A. Siwabessy research reactor with neutron flux of 5x1013 neutrons.m2.s-1. Post-irradiation samples were analyzed using gamma spectrometry. The results show that the aluminum contents in each foodstuff from one region have a strong correlation with other regions (Pearson correlation coefficient r>0.9, P<0.001), indicating that the distribution of aluminum content does not differ from one region to another. The staple food category has a relatively low aluminum content with an average value of 24 mg/kg and a maximum value of 35 mg/kg. The dish category has higher aluminum content with an average value of 51 mg/kg and a maximum value of 77 mg/kg. The vegetable category has the highest content with an average value of 156 mg/kg and a maximum value of 710 mg/kg owned by caisim. Caisim is interesting for further research because of its ability to store large amounts of several elements. In general, the intake of aluminum sourced from these foods is still below the allowed value.Keywords: Neutron activation analysis, Food safety and security, Alzheimer, Aluminum distribution, Pearson correlation